2002
DOI: 10.2337/diacare.25.12.2335
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Resistance Exercise Training to Improve Glycemic Control in Older Adults With Type 2 Diabetes

Abstract: OBJECTIVE -To determine the efficacy of high-intensity progressive resistance training (PRT) on glycemic control in older adults with type 2 diabetes.RESEARCH DESIGN AND METHODS -We performed a 16-week randomized controlled trial in 62 Latino older adults (40 women and 22 men; mean Ϯ SE age 66 Ϯ 8 years) with type 2 diabetes randomly assigned to supervised PRT or a control group. Glycemic control, metabolic syndrome abnormalities, body composition, and muscle glycogen stores were determined before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
553
8
74

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(684 citation statements)
references
References 37 publications
34
553
8
74
Order By: Relevance
“…Although we could not measure sarcopenia among our patients, the relationship found between lower muscle strength and a poor protein diet (MNA item 11) in our participants would account for the lack of function, hence affecting HRQoL. Thus, increases in skeletal muscle mass, or even muscle function (34) are not only related to glycemic control (35,36) but it also appears to be important for prevent the decline in function among T2DM patients, particularly with aging. Consequently, efforts should be made to increase physical exercise, which may lead to improvements in muscle strength, in the T2DM population.…”
Section: Discussionmentioning
confidence: 92%
“…Although we could not measure sarcopenia among our patients, the relationship found between lower muscle strength and a poor protein diet (MNA item 11) in our participants would account for the lack of function, hence affecting HRQoL. Thus, increases in skeletal muscle mass, or even muscle function (34) are not only related to glycemic control (35,36) but it also appears to be important for prevent the decline in function among T2DM patients, particularly with aging. Consequently, efforts should be made to increase physical exercise, which may lead to improvements in muscle strength, in the T2DM population.…”
Section: Discussionmentioning
confidence: 92%
“…Inclusion criteria included type 2 diabetes mellitus as defined by the American Diabetes Association [13] for at least 6 months and baseline HbA 1c of 6.6% to 9.9%. Potential participants were excluded if they: (1) were receiving insulin therapy; (2) were participating in exercise ≥2 times per week for at least 20 min per session or had been in any resistance training during the previous 6 months; (3) reported changes in oral hypoglycaemic medications during the previous 2 months; (4) reported changes in antihypertensive or lipidlowering agents in the previous month; (5) reported a change of ≥5% in body weight during the previous 2 months; (6) had serum creatinine ≥200 μmol/l; (7) had proteinuria >1 g/24 h; (8) had blood pressure >160/95 mmHg; (9) had restrictions in physical activity due to disease; (10) had other medical conditions making participation inadvisable; or (11) completed fewer than ten of the 12 scheduled exercise sessions during the run-in period.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analyses and other studies have demonstrated that aerobic and resistance exercise each improves glycaemic control in people with this condition [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to its important effect on glycemic control, resistance training is a very important intervention because it counteracts the exacerbated loss of muscle strength and functional capacity observed in elderly patients (Castaneda et al 2002;Dunstan et al 2002;Brooks et al 2007;Ibañez et al 2008;Geirsdottir et al 2012). For example, in study of Brandon et al (2003), 24 weeks of resistance training performed at moderate intensity induced increases in muscle strength and mobility in elderly with type 2 diabetes.…”
Section: Functional Capacity In Elderly Diabetic Patientsmentioning
confidence: 99%